Process Skills-Based E-Module: Impact On Analytical Thinking Skills - Maison Maison; Dwi Agus Kurniawan; Ricky Purnama Wirayuda; Diki Chen (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2022)
This study aims to determine the E-Module practicum application based on science process skills for high school students on temperature and heat material, describe students’ analytical thinking skills, and identify the effect of science process skills on students’ analytical thinking. Temperature and heat material skills in physics subjects at school. This study uses a mixed-method with an explanatory design. Data collection was carried out in April-May 2021 at senior high school 10 Muaro Jambi. The population of this study was all students of class X public Senior High School (SMAN) 10 Muaro Jambi. The research sample used was 30 science class students consisting of X science 1, X science 2, and X science 3 SMAN 10 Muaro Jambi. The sampling technique used is random sampling. The instruments used in this study were scientific process skills observation sheets and analytical thinking skills assessment questions. The regression analysis was used to determine how the variables were used. This study obtained the results after students used a practical guide based on science process skills. Students had good science process skills. The science process skill variable affected the students’ analytical thinking ability by 52.2%, and other variables influenced the remaining 47.8%. The impact of the research that researchers expect is that teachers can innovate the learning process using e-modules based on science process skills to improve other abilities possessed by students.